1995
DOI: 10.1182/blood.v85.10.2770.bloodjournal85102770
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of T-progenitor cell activity within the CD34+ compartment of adult bone marrow

Abstract: T-cell production is largely dependent on the presence of a thymus gland where CD34+ precursors mature into T lymphocytes. Prethymic stages of T-cell development are less defined. Therefore, this study aims to delineate T-progenitor cell potential within the CD34+ Lineage-- (Lin-) cell compartment of adult bone marrow (ABM). Fractionation of CD34+ Lin-ABM cells with CD45RA, Thy-1, CD38, and HLA-DR failed to absolutely segregate T-cell reconstituting ability, indicating broad distribution of T-progenitor cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Investigators have used SCID-hu mice as model systems for the study of human stem cell phenotype and differentiation [42][43][44][45][46][47][48][49][50][51][52], human gene therapy protocols [53][54][55], human T-cell differentiation [56], and homing of human myeloma cells to the bone marrow [57]. SCID-hu mice, in combination with cotransplanted thymic fragments, have been used to investigate the primitive hemopoietic stem cell that populates the T-cell lineage [42,58], for studies of human T-cell function [59,60], and for infection of human T cells and thymus with HIV [61,62]. Although an important experimental system, human fetal tissues are not readily available and impose a number of ethical concerns and constraints that limit their widespread use among laboratories.…”
Section: Scid-hu Micementioning
confidence: 99%
“…Investigators have used SCID-hu mice as model systems for the study of human stem cell phenotype and differentiation [42][43][44][45][46][47][48][49][50][51][52], human gene therapy protocols [53][54][55], human T-cell differentiation [56], and homing of human myeloma cells to the bone marrow [57]. SCID-hu mice, in combination with cotransplanted thymic fragments, have been used to investigate the primitive hemopoietic stem cell that populates the T-cell lineage [42,58], for studies of human T-cell function [59,60], and for infection of human T cells and thymus with HIV [61,62]. Although an important experimental system, human fetal tissues are not readily available and impose a number of ethical concerns and constraints that limit their widespread use among laboratories.…”
Section: Scid-hu Micementioning
confidence: 99%
“…Il s'agit, en premier lieu, des travaux pionniers de Shaper et al [20] et de Bernstein et al [21] qui ont permis l'identification de la molécule CD34 1 comme un marqueur membranaire des cellules du compartiment hématopoïétique immature, incluant les CSH, les progéniteurs et les précurseurs hématopoïétiques, et, en second lieu, des travaux de Gabner et al [22] qui ont montré que l'expression différentielle de CD45RA permettait de distinguer le compartiment des CSH et des progéniteurs érythro-mégacaryocytaires (n'exprimant pas ce marqueur, CD45RA -), de celui des progéniteurs lympho-granulo-macrophagiques. Ces résultats, rapidement confirmés par Chen et al [23], ont abouti, deux ans plus tard, en 1995, à l'identification de la première population de progéniteurs lymphoïdes [1]. Cette population, isolée à partir de la moelle osseuse de donneurs adultes, se caractérisait par son phénotype (CD34 + CD45RA + CD10 + ), par un triple potentiel de différenciation en lymphocytes B, T et en cellules NK (natural killer), et par son incapacité à générer des cellules érythroïdes et granulo-macrophagiques en culture in vitro.…”
Section: Architecture Développementale De La Lymphopoïèse Humaineunclassified
“…As noted, CD45RA is absent on LTC‐IC and populations enriched for erythroid‐committed progenitors. Thus, the Lin – CD34 + CD45RA + surface immunophenotype was used to identify a population of cells enriched for lymphoid and myeloid potential but which possessed neither erythroid potential nor the ability the ability to provide long‐term repopulation in xenograft (56). The significant lymphoid capacity of this population suggested that it might contain a CLP as well as committed lymphoid and myeloid progenitors (11).…”
Section: Identification Of Lineage Restricted Progenitorsmentioning
confidence: 99%